(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the problematic behavior and emotional deprivation among middle school students, as well as the significant differences in problematic behavior and emotional deprivation in terms of gender and specialization (scientific-literary). To achieve the research objectives, the researcher developed a scale to measure problematic behavior, consisting of 30 items, and a scale of emotional deprivation, consisting of 30 items with five alternatives. The research sample consisted of 300 male and female students who were chosen randomly from middle and secondary schools in the city of Tikrit. It used the following statistical methods: chi-square, Cronbach’s Alpha, t-test for one sample, t-test for two independent samples, and analysis of variance. The results showed that the research sample has problematic behavior and emotional deprivation. There are no significant differences in problematic behavior and emotional deprivation among students in terms of gender and specialization. There is a significant positive correlation between problematic behavior and emotional deprivation. Based on these results, the researcher came out with a set of recommendations and suggestions.